Targeting Death Receptor 5 (DR5) for the imaging and treatment of primary bone and soft tissue tumors: an update of the literature - Gamie, Zakareya; Krippner-Heidenreich, Anja; Gerrand, Craig; Rankin, Kenneth Samora (Frontiers in Molecular Biosciences, 2024)
Background: Death Receptor (DR) 5 is expressed on the surface of primary bone and soft tissue sarcoma cells and its activation induces cell death primarily through apoptosis.Combination of DR5 agonists with commonly used chemotherapeutic agents such as doxorubicin can promote cell death. Presently clinical trials are investigating the effectiveness of DR5 activation using new biological agents such as bi-specific or tetravalent antibodies in improving the survival of patients with relapsed or refractory cancers. Furthermore, investigations continue into the use of novel combination therapies for enhancing DR5 response, for example, with Inhibitor of Apoptosis Protein (IAP) antagonist agents [such as second mitochondria-derived activator of caspase (smac) mimetics] and with immune checkpoint inhibitor anti-programmed death-ligand 1 (anti-PD-L1) or antiprogrammed cell death 1 (anti-PD-1) antibody. Other therapies include nanoparticlemediated delivery of TRAIL plasmid DNA or TRAIL mRNA and stem cells as a vehicle for the targeted delivery of anti-cancer agents such as TRAIL to the tumour. Methods: Scoping review of the literature from November 2017 to March 2024 utilising PubMed and Google Scholar. Results: New agents under investigation include NanoTRAIL, anti kv10.1, Multimeric IgM and humanised tetravalent antibodies. Developments have been made to test novel agents and imaging has been used to detect DR5 in preclinical models and patients. The models include 3D spheroids, genetically modified mouse models, a novel jaw osteosarcoma model and patient-derived PDX animal models. There are currently two ongoing clinical trials focussing on the activation of DR5, namely, IGM-8444 and INBRX-109, which have progressed to phase 2. Further modifications of TRAIL delivery with fusion to single-chain variable fragments (scFv-TRAIL), directed against tumour-associated antigens (TAA) and in the use of stem cells focus on targeted TRAIL delivery to cancer cells using bi-functional strategies. Conclusion: In vitro, in vivo and clinical trials as well as advances in imaging and theranostics indicate that targeting DR5 remains a valid strategy in the treatment of some relapsed and refractory cancers.